All activity-oriented approach in teaching geometry - Milo, Gracia Agilada 1949-
This study compared two third year classes, one taught by an activity-oriented method, the other through traditional non-activity approach using lectures, question and answer type, rules and procedure. It determined the relative effects of the two methods on the achievement and attitude of students in Geometry.